Labour Contracts and Labour Relations in Early Modern Central Japan - Nagata, Mary Louise (Changing Labour Relations in Asia, 2005)
Based on a collection of labour contracts and other documents, this book examines the legal, economic and social relations of labour as they developed in the commercial enterprises of Tokugawa Japan. The urban focus is Kyoto, the cultural capital and smallest of the three great cities of the Tokugawa period, but the data comes from a wider region of commercial and castle towns and rural villages in central Japan.